A Comparison Between the Open Posterior Approach and Arthroscopic Suture Fixation in Treating Posterior Cruciate Ligament Tibial Avulsion: A Systematic Review - Kuswara, Leonardus William; Astawa, Putu; Aryana, I Gusti Ngurah Wien (Indonesian Journal of Global Health Research, 2024)
Posterior cruciate ligament (PCL) avulsion fractures are rare but significant injuries that can lead to knee instability and degeneration if untreated. Treatment options range from conservative management to surgical fixation. The objective of this study is to evaluate and compare the outcomes of different treatment modalities for posterior cruciate ligament (PCL) avulsion fractures, with a focus on surgical interventions, specifically open surgery and arthroscopy. Methods: A systematic literature search was conducted using the MEDLINE, EMBASE, and Cochrane Library databases from August 17, 2003 to August 17, 2023. Studies included involved patients with PCL avulsion fractures treated via arthroscopic or open fixation. Data was extracted on demographics, surgical approaches, outcomes (Lysholm scores), and complications. The Coleman methodology score was applied to assess study quality by scoring factors like study size, design, follow-up, and outcome measures, and only studies scoring ≥60 were included for data analysis. Results: Out of 1,470 studies, 12 met the inclusion criteria. Lysholm scores ranged from 85 to 100 for open approaches and 80 to 100 for arthroscopic approaches. Arthroscopic treatment showed fewer complications, such as infections or hardware irritation, while both approaches demonstrated favorable outcomes. Postoperative limitations in motion were observed in both groups, with a slightly higher incidence in the arthroscopic cohort. Conclusions: Both arthroscopic and open surgical approaches effectively treat PCL avulsion fractures, with arthroscopy showing a slight advantage in postoperative outcomes and fewer complications. However, open surgery with a small open procedure also offers satisfactory results, particularly for complex fractures.